Benjamin Shambaugh and the intellectual foundations of public history - Conard, Rebecca (Iowa City : University of Iowa Press, 2002)
Conard draws upon an unpublished, mid-1940's biography by research historian Jacob Swisher to trace the forces that shaped Shambaugh's early years, his administration of the State Historical Society of Iowa, his development of applied history and commonwealth history in the 1910's and 1920's, and the transformations in his thinking and career during the 1930's. Framing this intriguingly interwoven narrative are chapters that contextualize Shambaugh's professional development within the development of the historical profession as a whole in the late nineteenth and early twentieth centuries and.
Foreword and Acknowledgments; Prologue; 1. From the New History to Applied History; 2.A Gift of Fate; 3. The Politics of Public Institutions; 4.A Deliberate Course; 5. The Commonwealth Conference; 6.A New Deal in the Game of Life; 7. The Emergence of the Modern Public History Movement; Abbreviations and Shortened Reference; Notes; Collected Works of Benjamin Shambaugh; Bibliography; Index
Includes bibliographical references (pages 227-237) and index.
Collected works of Banjamin Shambaugh": pages 219-226
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Shambaugh, Benjamin Franklin, -- 1871-1940.; Shambaugh, Benjamin Franklin, -- 1871-1940.; Shambaugh, Benjamin Franklin, -- 1871-1940; Historians -- United States -- Biography; Historians -- Iowa -- Biography; Public history -- United States; Public history -- Iowa; United States -- Historiography; Iowa -- Historiography; Historians -- United States -- Biography; Historiens -- États-Unis -- Biographies; Historiens -- Iowa -- Biographies; Histoire appliquée -- États-Unis.; Histoire appliquée -- Iowa; États-Unis -- Historiographie; Iowa -- Historiographie; Historiens -- États-Unis -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- State & Local -- General; Historians; Historiography; Public history; Iowa; United States; Biography; Biographies; Biographies; Biographies